Scale-sensitivity analysis for floating energy production system with anti-motion structure under high sea conditions - Yuan, Hongtao; Chen, Yi; Li, Mingxin; Chen, Linfeng; Bai, Xu; Li, Yongzheng (Frontiers in Energy Research, 2024)
The heave motion of a new cylindrical floating drilling production storage and offloading system (FDPSO) with extended cylinder, anti-motion structure and a gap between the extended cylinder and anti-motion structure under high sea conditions was investigated by implementing numerical simulations for its reduced-scale laminar flow model (1:77.8) using the CFD software STAR-CCM+. The effect of changing the width (10 ∼ 15 m) and height (10 ∼ 15 m) of the anti-motion structure on the heave motion of the new cylindrical FDPSO were analyzed. The results show that increasing the width and height of the anti-motion structure increases the natural period of the structural heave motion, making it far away from the main energy period of the wave, and has a certain inhibitory effect on the heave motion of the FDPSO. Comparing the variation of vortex field around the structures of different sizes, it is concluded that the vortex generation and vortex shedding around the highwidth anti-motion structure model is significantly strengthened compared with the low-width anti-motion structure model. The variation of the vortex generation and vortex shedding due to the change in height is relatively inferior compared to the change in width.